The importance of disability representation to address implicit bias in the workplace - Derbyshire, Daniel W.; Spencer, Anne E.; Grosskopf, Brit; Blackmore, Theo (Frontiers in Rehabilitation Sciences, 2023)
People are disabled by barriers in society, not by their impairment. Barriers can be physical or be caused by people's implicit and explicit attitudes towards people with disabilities. We utilise the Implicit Association Test to investigate implicit attitudes towards people with disabilities among Human Resource professionals and people involved in making hiring decisions. We find no significant differences between people who work for large companies or Small- to Medium-sized Enterprises. Similarly, working in Human Resources (or making recruitment decisions) has no effect on implicit bias. We supply the first evidence linking a person’s own health status (measured using EQ-5D-5L) to their implicit bias. We find that a worse health status is associated with lower implicit bias towards people with disabilities. In addition, we find women have lower implicit bias than men. The discussion reflects on the need for greater disability representation within the workplace – especially in making hiring decisions.